Hypermarket corporate brand extension personality - Hasliza Hassan, Hassan; Rahman, Muhammad Sabbir; Abu Bakar Sade, Sade (North American Business Press, 2014)
Products and services are complementary to each other. This research explores the relationship of hypermarket corporate brand extension of products and services as parallel independent constructs towards brand personality. Through convenience sampling of hypermarket distribution outlets throughout Malaysia, 785 data were collected from hypermarket consumers based on proportionate quota. The collected data were analysed using exploratory factor analysis, confirmatory factor analysis and structural equation modeling. It is proven that both the products and services that are offered by the hypermarkets are equally important in influencing the hypermarket corporate brand personality.